Highly stable COF-supported Co/Co(OH)(2) nanoparticles heterogeneous catalyst for reduction of nitrile/nitro compounds under mild conditions - Mullangi, Dinesh; Chakraborty, Debanjan; Pradeep, Anu; Koshti, Vijay; Vinod, Chathakudath P.; Panja, Soumendranath; Nair, Sunil; Vaidhyanathan, Ramanathan (Small, 2018)
Ordered nanoporosity in covalent organic framework (COF) offers excellent opportunity for property development. Loading nanoparticles (nPs) onto them is one approach to introducing tailor-made properties into a COF. Here, a COF-Co/Co(OH)(2) composite containing about 16 wt% of <6 nm sized Co/Co(OH)(2) nPs is prepared on a N-rich COF support that catalyzes the release of theoretical equivalence of H-2 from readily available, safe, and cheap NaBH4. Furthermore, the released H-2 is utilized for the hydrogenation of nitrile and nitro compounds to amines under ambient conditions in a facile one-pot reaction. The COF "by choice" is built from "methoxy" functionalized dialdehydes which is crucial in enabling the complete retention of the COF structure under the conditions of the catalysis, where the regular Schiff bonds would have hydrolyzed. The N-rich binding pockets in the COF ensure strong nP-COF interactions, which provides stability and enables catalyst recycling. Modeling studies reveal the crucial role played by the COF in exposing the active facets and thereby in controlling the activation of the reducing agent. Additionally, via density functional theory, we provide a rational explanation for how these COFs can stabilize nanoparticles which grow beyond the limiting pore size of the COF and yet result in a truly stable heterogeneous catalyst - a ubiquitous observation. The study underscores the versatility of COF as a heterogeneous support for developing cheap and highly active nonnoble metal catalysts.